2020
DOI: 10.1111/edt.12564
|View full text |Cite
|
Sign up to set email alerts
|

Storage of an avulsed tooth prior to replantation: A systematic review and meta‐analysis

Abstract: Background/Aim It is crucial to store an avulsed tooth appropriately to preserve the viability of the periodontal ligament cells prior to replantation. The aim of this systematic review was to identify the best available evidence for the effectiveness of any technique available to laypeople for storing an avulsed tooth compared with storage in milk or saliva. Methods The following databases were searched (September 2019): Cochrane Library, MEDLINE, and Embase. Two reviewers independently considered trial eligi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 61 publications
(164 reference statements)
1
53
0
13
Order By: Relevance
“…Forty‐four SRs had been published in last six years (2015‐2020) 18‐78 . Twenty‐eight of the SRs had been published in Dental Traumatology, 16,17,20‐27,29,30,36,39‐41,44,45,59,60,67,69,71,74,75,77,78 and five were from the Cochrane database 38,46,50,53,70 . The remaining SRs were spread across journals in general dentistry, sports medicine, orthodontics, special care dentistry, endodontics, maxillofacial radiology, oral and maxillofacial surgery, pediatric dentistry, oral sciences, periodontology, community dentistry, epidemiology, dental hygiene, education sciences, and restorative dentistry (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty‐four SRs had been published in last six years (2015‐2020) 18‐78 . Twenty‐eight of the SRs had been published in Dental Traumatology, 16,17,20‐27,29,30,36,39‐41,44,45,59,60,67,69,71,74,75,77,78 and five were from the Cochrane database 38,46,50,53,70 . The remaining SRs were spread across journals in general dentistry, sports medicine, orthodontics, special care dentistry, endodontics, maxillofacial radiology, oral and maxillofacial surgery, pediatric dentistry, oral sciences, periodontology, community dentistry, epidemiology, dental hygiene, education sciences, and restorative dentistry (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining SRs were spread across journals in general dentistry, sports medicine, orthodontics, special care dentistry, endodontics, maxillofacial radiology, oral and maxillofacial surgery, pediatric dentistry, oral sciences, periodontology, community dentistry, epidemiology, dental hygiene, education sciences, and restorative dentistry (Table 3). The highest number of systematic reviews had been performed in the domain of Prognostics (n = 19) 47‐65 followed by the domain of Epidemiology (n = 15), 12,18‐31 the domain of Therapeutics (n = 10), 17,38‐46 the domain of Oral Biology (n = 7), 72‐78 the domain of Diagnostics (n = 6), 32‐37 the domain of Preventive (n = 5), 66‐70 and the domain of Research Methods (n = 2) 16,71 …”
Section: Resultsmentioning
confidence: 99%
“…When an injury causes tooth avulsion (ie, the tooth is pulled out with the root), the tooth must be stored in an appropriate medium to preserve viability until the tooth can be reimplanted. The First Aid Task Force sought a 2020 SysRev 111 to identify optimal media for temporary tooth storage, comparing the effects of many different media on periodontal ligament cell viability (surrogate for viability of the tooth for reimplantation). Although milk remains an effective medium, the task force concluded that other media as well as the use of clear cling film (ie, plastic wrap) were more effective in preserving viability.…”
Section: First Aidmentioning
confidence: 99%
“…The First Aid Task Force requested a 2020 SysRev of media used to store an avulsed tooth until it can be reimplanted. 111 Many RCTs found benefit from immersion of the tooth in Hanks’ Balanced Salt Solution 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 as well as in oral rehydration salt solutions 154 , 155 or from wrapping the tooth in cling film (ie, plastic wrap) 158 as compared with immersion in milk. However, milk was better than many other media for storing a tooth until reimplantation.…”
Section: First Aidmentioning
confidence: 99%
“…The periodontal ligament cells’ vitality is the most important factor to allow the reattach following tooth replantation [ 1 ]. Furthermore, other factors like extraoral time, storage of the avulsed tooth, and maturity of the root are also important to dental prognosis [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%